Peningkatan Perhatian dan Hasil Belajar IPA Melalui Penerapan Model Quis Team Pada Siswa Kelas V SDN 06 Sragen Tahun 2015/2016 - SITA UMARA, ADNA (2016)
Their attention to a teacher, the learning process is very focused. From observations made problems arising in SDN 06 Sragen is a classic problem. The problem faced by them is the low attention of learners in science learning. The lack of enthusiasm of students in science subjects. The low value of learners in science learning. The purpose of this research to improve the care and outcomes of learning science through learning model Quis Team in the fifth grade students of SDN 06 Sragen Year 2015/2016. This type of research conducted by researchers is a qualitative descriptive research. The subjects of this study were teachers and students of class V SD Negeri 6 Sragen Year 2015/2016. The data collected in this study a quantitative and qualitative data. Source of data obtained from: Attention students of class V SDN 06 Sragen, a class V student learning outcomes SDN 06 Sragen, fifth grade teacher at SDN 06 Sragen. Data collection techniques such as; observation, interviews, documentation, test. Data analysis techniques, namely; data collection, data reduction, presentation of data, verification data. Procedure early dialogues research, planning, implementation, observation and reflection. Based on the results of a classroom action research conducted, the results of the study can be summarized as follows: Attention students in the learning process of each cycle is performed has increased. In Pre Cycle of 37.83%, in the first cycle was 45.94%, in Cycle II amounted to 70.27%. While the results of students in science subjects of each cycle is carried out in accordance with the increased minimum completeness criteria (KKM) 70. At the Pre Cycle of 37.83%, In the first cycle was 48.64%, in the second cycle of 91.89 %